Identifikasi Motivasi Belajar Siswa Kelas XII IPA pada Mata Pelajaran Fisika di SMA Negeri 10 Kota Jambi - Sisca Agustin; Nurmaliza Nurmaliza; Amril Sastra; Wella Meliza; Mesi Loviya (Universitas PGRI Semarang, 2021)
This study aims to identify the learning motivation of class XII IPA students in the physics subject at SMA Negeri 10 Jambi City. The existence of motivation that each student has is the influence of the factors that occur in students, a high learning environment factor will be highly motivated to learn and will also have a good effect on learning outcomes. This type of research is quantitative research using a descriptive approach. The instrument used was a questionnaire or a questionnaire. The research was conducted at SMA Negeri 10 Jambi City. The population of this study were students of class XII IPA 1, XII IPA 2 and XII IPA 3 in SMA Negeri 10 Jambi City. The sampling technique used purposive sampling technique, namely the sampling technique based on research criteria. The method used in this research is descriptive statistics where the research method is aimed at describing the existing phenomena without any engineering or manipulation of the situation. The results of this study indicate that the motivation to learn Physics class XII IPA students have good learning motivation. A good education will be good for the environment around us. Good motivation will have a strong spirit in the learning process.